Removal of Chemical Oxygen Demand in Brackish Water by Rhizophora mucronata using Reed Bed System Batch Reactor - Titah Harmin Sulistiyaning; Purwanti Ipung Fitri; Pratikno Herman; Chimayati Rachmi Layina; Handayanu (E3S Web of Conferences, 2019)
River pollution can cause coastal pollution due to many pollutants can not remove during water flow from upstream to downstream. River has a capability to do self purification to remediate many pollutans, but wastewater disposal occurred at along the river. One of pollution parameter that caused by organic pollutant was Chemical Oxygen Demand (COD). In this research, the design of reactor was adapted from reed bed system commonly used in constructed wetlands. The purpose of the study was to determine the COD removal by Rhizophora mucronata using reed bed system reactor. There were 8 reactors, with duplo replicates, namely RM15 and RM 25 for treatment with Rhizophora mucronata at 15 ‰ and 25 ‰, respectively, and RMVA15 and RMVA 25 for treatment with Rhizophora mucronata and addition of Vibrio alginolyticus, respectively. Parameter of COD was determined using digestion reactor and spectrophotometer. Based on the results, the highest removal of COD reached 82.06% after 14 days at reactor of RM15. The highest of removal COD with addition of Vibrio alginolyticus was 80.89% after Day 2 at reactor of RMVA15. In conclusion, the Rhizophora mucronata that was grown at reed bed system reactor demonstrated can be used in removing organic matter.